THE FOREST WARRIOR OF WALISONGO ISLAMIC BOARDING SCHOOL TUBAN: Supporting Students as Ecotheology Based Forest Conservator - Mahzumi, Fikri; Suhermanto, Suhermanto; Iffah, Iffah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
This study tried to explore the subject of Noer Nasroh Hadiningrat who had found an eco-theological awareness at the Walisongo Islamic Boarding School in Tuban. Ecotheology is an interesting topic in academic studies today. The ecological paradigm that rests on the spirit of this religion is believed to be able to overcome the environmental crisis happening now. The focus of this study seeks to explain how the subject's conception of ecotheology, what actions are carried out? And how sustainability and implications are for the community? Using an ethnographic approach, this study focuses on epic and emic data obtained from the explanation of the subject and facts in the research field. The results of this study found that the ecotheology conception initiated by the subject was a religious reflection that originated from the primary text of Islam combined with traditional wisdom. The establishment of the State Vocational High School (SMKN) is a concrete manifestation of the subject's efforts to integrate beliefs, traditions, and forestry so that they manifest themselves in concrete actions such as reforestation, conservation, and changes in public awareness of the urgency of forest conservation. In the aspect of continuity, the existence of Forestry Vocational Schools is a forum for printing students who have an awareness of forest conservation as well as being able to seek life from it. The idea of Kiai Noer also received support from sons, the government, and the community. This ecotheology conception has also inspired other pesantren to form a similar ecological paradigm.